Increased Yield and Improved Transplantation Outcome of Mouse Islets with Bovine Serum Albumin - Suzanne Bertera; A. N. Balamurugan; Rita Bottino; Jing He; Massimo Trucco (Journal of Transplantation)
Isolation and transplantation of rodent islets are frequently used as a tool for predicting the behavior of new protocols for islet allotransplants in type 1 diabetes patients. Bovine serum albumin (BSA) is recognized as a protease inhibitor possibly protecting function and viability in islets. For this study, the addition of 0.2% BSA to the isolation protocol resulted in a 30% increase in islet yields while other parameters, such as viability and function, retained high islet quality. In vivo, a minimal mass of 70 BSA treated islets showed their ability to control glycemia levels in diabetic mice by bringing the average blood glucose to 153±13.2 mg/dL compared to 288±22.6 mg/dL without BSA. Our results show that the simple addition of BSA to the isolation protocol constitutes a reliable and reproducible method for increasing islet yield. Also adding BSA to the transplantation medium improves islet function in vivo. The method outlined here can reduce the overall number of animals needed per experiment and also reduce the time and resources needed for islet preparation.